1967
DOI: 10.1084/jem.126.6.1127
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Stroma-Free Hemoglobin Solution for Use as a Plasma Expander

Abstract: Plasma, dextran, and other preparations, although effective as plasma expanders, cannot carry oxygen and therefore are not as useful as whole blood for management of acute hemorrhage. Blood, on the other hand, has a limited storage time and must be typed and cross-matched prior to use. Hemoglobin in solution has several unique properties which could be desirable for treating hemorrhagic shock. In addition to its osmotic activity (tool wt 68,000), hemoglobin can transport and exchange oxygen and has the advanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1
6

Year Published

1970
1970
2005
2005

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(50 citation statements)
references
References 33 publications
(40 reference statements)
1
42
1
6
Order By: Relevance
“…4). Previous studies have shown that the liver is also the site of removal of protein-bound heme in animals (21,22) and of free and haptoglobin-bound hemoglobin in animals (35,43,48) and man (15,16 Reutilization of heme-iron (Fig. 4).…”
Section: Disposal Of Plasma Hemementioning
confidence: 99%
“…4). Previous studies have shown that the liver is also the site of removal of protein-bound heme in animals (21,22) and of free and haptoglobin-bound hemoglobin in animals (35,43,48) and man (15,16 Reutilization of heme-iron (Fig. 4).…”
Section: Disposal Of Plasma Hemementioning
confidence: 99%
“…Their main known disadvantages are, reduced circulation half-life, haemodynamic and gastrointestinal perturbations, probably related to nitric oxide (NO) scavenging, free radical induction, and alterations of biochemical and haematological parameters (increase in liver enzyme levels, platelet aggregation) [1][2][3].…”
Section: Mjafi 2003; 59 : 45-50mentioning
confidence: 99%
“…Stroma-free solutions of hemoglobin have been shown to be free of toxic effects such as deterioration of kidney function and coagulation disorders (Palani et al, 1975;Rabiner et al, 1967;Relihan and Litwin, 1973). The two major disadvantages are short intravascular persistence and high oxygen affinity (Sunder-Plassmann et al, 1975).…”
Section: Discussionmentioning
confidence: 99%